Maqasid Shari’ah Analysis of Shari’ah Bank Services in Makassar City - Rahmawati Rahmawati; Rahman Syamsuddin; Subehan Khalik (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research aims to analyse the application of Maqasid Shari'ah principles in the services of Bank Syariah Indonesia (BSI) in Makassar City and its impact on customer satisfaction. This research uses a qualitative approach with normative juridical, normative theological (shar'i), and sociological methods. Data were collected through interviews, observation, and documentation with BSI and customers, as well as secondary data from related literature. The research findings show that BSI is committed to implementing maqasid shari'ah through services that prioritise the benefit, social justice and welfare of the people, such as the shari'ah education financing programme and worship services. Despite challenges related to the public's understanding of shariah banking, the majority of customers are satisfied with services that comply with shariah principles, despite complaints about mobile applications and ATM access. The implication of this study is the need for further development in customer education and improvement of service facilities to further optimise the implementation of maqasid shari'ah, as well as providing insights for shari'ah financial institutions in improving services that are more equitable and in accordance with Islamic principles.